Can America Police the World? - Rubin, Alfred P. (Tufts Archival Research Center, 2005)
Volume 13, Issue 2. Summer A Lebanese terrorist was recently convicted in a US court for hijacking a Jordanian airliner. Although the Americans on board the plane were unharmed, the FBI orchestrated an elaborate maneuver and captured the terrorist on board a Cypriot vessel in international waters. Alfred P. Rubin argues that such an extraterritorial application of US criminal law was a serious mistake, violating international law. He maintains that the international political implications of such legal maneuverings are more important than the arrest or conviction of a single terrorist